Pemberdayaan Kelompok Wanita Tani (KWT) Tunas Berkah Kota Blitar dengan Metode Parcipatory Rural Appraisal - Puspitorini, Palupi; Purwatiningsih, Rini; Sunandes, Aris (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
Community empowerment is a way to increase and strengthen community skills to participate in development which is carried out energetically. The expected result is that the community can resolve the problems experienced in a more flexible (independent) and self-sufficient way. The community empowerment approach that is realized in development in a participatory manner (Participatory Rural Appraissal) is very suitable for business groups so that they can then overcome problems that arise. in group activities. The partner of this service is the Tunas Berkah Women's Farmers Group which operates in the field of vegetable plant breeding, which is domiciled in RW 04 Gedog Village, Sananwetan District, Blitar City. Service Objectives: to form partners who are more productive and have a high entrepreneurial spirit and values, to improve students' experience of studying outside campus as one of the implementations of MBKM. Implementation of activities includes program planning, administrative preparation and team coordination, Continuous assistance from pre-production to post-production, Activity Evaluation and Control. The results of the activities achieved are Overcoming seed production problems, overcoming business management and human resource problems, Overcoming seed marketing problems. Using the PRA method, FGD activities, PRA training/socialization, nursery cultivation training, nursery business management training, and marketing have been carried out which can increase the capacity of groups with larger business scales that have an organizational and economic impact.